(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Urinary tract aspergillosis is uncommon even in the era of increased frequency of invasivemycoses. Experience is largely from isolated case reports and few case series or reviews.The majority of cases involve transplant recipients predominantly following renaltransplantation but is also reported in other immunocompromised states such as AIDS anduncontrolled diabetes mellitus. Most cases represent haematogenous spread to renalparenchyma, often in the absence of recognized focus of infection, presenting as small orlarge abscesses, infarcts, renal insufficiency or urinary drainage system fungal balls withobstructive uropathy. Diagnosis is usually made on the basis of renal tissue aspiration, urinecultures or by histopathology of the suspicious mass passed through urinary tract. Theeffective management of invasive aspergillosis includes strategies to optimize preventionand early antifungal treatment, immunomodulation, and, in some cases, surgery. Neweranti-Aspergillus drugs notably voriconazole offer less toxic therapeutic options and are quitesuccessful in combination with drainage measures to relieve urinary stasis. This reportdescribes a case of primary urinary tract aspergillosis with fungal bezoars formation in a 37years old female, diabetic, hypertensive, who presented with intermittent urinary tractobstruction and was successfully managed by oral voriconazole for six weeks as itraconazolewas found refractory. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 74-77